2015
DOI: 10.1007/s10741-015-9522-7
|View full text |Cite
|
Sign up to set email alerts
|

Partial adenosine A1 receptor agonism: a potential new therapeutic strategy for heart failure

Abstract: Heart failure (HF) represents a global public health and economic problem associated with unacceptable rates of death, hospitalization, and healthcare expenditure. Despite available therapy, HF carries a prognosis comparable to many forms of cancer with a 5-year survival rate of ~50%. The current treatment paradigm for HF with reduced ejection fraction (EF) centers on blocking maladaptive neurohormonal activation and decreasing cardiac workload with therapies that concurrently lower blood pressure and heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…Adenosine therapy is cardioprotective for chronic heart failure mediated by A 1 and A 3 receptors. 117 A 1 receptor activation attenuates cardiac hypertrophy and prevents heart failure in a mouse left-ventricular pressure-overload model and in a rat neonatal cardiac myocyte model. 118 K ATP channels are critical for maintaining myocardial perfusion and highenergy phosphates in the failing heart.…”
Section: Heart Diseasesmentioning
confidence: 99%
“…Adenosine therapy is cardioprotective for chronic heart failure mediated by A 1 and A 3 receptors. 117 A 1 receptor activation attenuates cardiac hypertrophy and prevents heart failure in a mouse left-ventricular pressure-overload model and in a rat neonatal cardiac myocyte model. 118 K ATP channels are critical for maintaining myocardial perfusion and highenergy phosphates in the failing heart.…”
Section: Heart Diseasesmentioning
confidence: 99%
“…7,8 The reason for the development of a partial adenosine A1-receptor agonist is that the use of full A1-receptor agonists in HF has been limited by undesirable cardiac effects such as negative inotropic, chronotropic, and dromotropic effects, including high-degree atrioventricular (AV) block, in particular with the concomitant use of -blockers. 8 In addition, a full agonist might have undesired extracardiac effects such as anti-diuretic effects (caused by vasoconstriction of the renal afferent arterioles) and neurological effects such as sedation. A partial adenosine A1-receptor agonist might overcome these undesired side effects while preserving the potentially beneficial cardioprotective effects of adenosine, depending on the tissue-specific receptor reserve for determined pharmacological effects and on the effects of endogenous adenosine.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Furthermore, non‐cardiac effects such as decreased neurotransmitter release in the central nervous system (CNS), resulting in sedation, for example, are known to be triggered by full A 1 R agonists. Therefore, partial A 1 R agonists might be beneficial as a new therapeutic option in treating HF . We previously reported that partial A 1 R agonists modulate and trigger primarily favorable pharmacological responses for HF therapy, such as improvement of left ventricular (LV) function and cardioprotection without evoking the adverse effects of full A 1 R agonists .…”
Section: Introductionmentioning
confidence: 99%